Placement of the Woven EndoBridge (WEB) device via distal transradial access in the anatomical snuffbox: A technical note. (November 2019) - Al Saiegh, Fadi; Mouchtouris, Nikolaos; Sweid, Ahmad; Chalouhi, Nohra; Theofanis, Thana; Ghosh, Ritam; Tjoumakaris, Stavropoula; Gooch, M. Reid; Rosenwasser, Robert H.; Jabbour, Pascal
Highlights: The distal transradial access in the anatomical snuffbox is new for neuro-interventions. It has lower rates of ischemia than the traditional femoral and radial access. It has mainly been used for diagnostic cerebral angiography and mechanical thrombectomy. We demonstrate its first use for aneurysm treatment using the WEB device. Abstract: The distal transradial access in the anatomical snuffbox for neurovascular procedures is a modification of the radial access with an improved safety profile and patient comfort compared to the conventional transradial access. However, its use has been limited to diagnostic cerebral angiography, but not aneurysm treatment. We present the first case of a 53-year-old female whose work-up for headaches showed an anterior communicating artery aneurysm. The patient underwent distal transradial cerebral angiography and subsequent placement of a Woven EndoBridge (WEB) device for treatment of the aneurysm through the same access site. The procedure was uneventful and the patient was discharged home neurologically intact. Her hand remained warm, well-perfused, and with no visible or palpable hematoma. Our report illustrates the feasibility of the distal TRA for the treatment of cerebral aneurysms using the WEB device. Further studies are necessary to confirm the additional benefits of the distal TRA over TRA for neurovascular access.